Developing e-modules based on scientific literacy in bamboo ethno-taxonomy - Siti Munawaroh; Ari Sunandar; Mahwar Qurbaniah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
The development of e-module materials for the classification of living things based on scientific literacy and bio-ethnotaxonomy issues is still very limited. This study aims to develop e-modules for the classification of living things based on scientific literacy and bamboo ethnotaxonomy that are valid and suitable for use in learning. This research and development was carried out using a 4D model by Thiagarajan. This study involved three material expert validators, three media expert validators, and three language expert validators. The instruments used include questionnaires and interview sheets. Development trials are carried out in small-scale trials and large-scale trials. A total of 24 students were involved in the trial with a division of 5 students in the small-scale trial, and 19 students in the large-scale trial. The results showed that there were four species of bamboo found in Sungai Krawang Village, including Bambusa vulgaris, Bambusa multiplex, Gigantochloa apus, and Gigantochloa atroviolacea. The results of material and linguistic validation show that the product developed has fulfilled four and six indicators with a score of >80% (very valid). Furthermore, the validation results of media experts are classified as very valid on three indicators including media size, cover design, and overall design with successive scores of 90.00, 83.33, and 84.76. These results indicate that the e-module of bamboo ethnotaxonomy is appropriate for use in learning about the classification of living things.